Quantification of Tau-A in serum after brain injury: a comparison of two analytical platforms, ELISA and electrochemiluminescence immunoassay. (12th May 2022) - Tzara, Ourania; Amalie Simonsen, Sofie; Sode West, Anders; Asser Karsdal, Morten; Klingenberg Iversen, Helle; Henriksen, Kim
ABSTRACT: Background: Previous studies have indicated the utility of the ADAM10-generated fragment of tau, Tau-A, as marker of neuronal damage. However, the sensitivity of the ELISA-based system was limited. Objectives: We utilized the extensive dynamic range of electrochemiluminescence compared to colorimetric assessment to improve the sensitivity of the Tau-A assay and investigate Tau-A levels after brain injury. Methods: We converted the Tau-A competitive ELISA to a competitive electrochemiluminescence-based immunoassay, Tau-A ECLIA, and compared the methods by measuring serum samples in a TBI (n = 40) and a stroke cohort (n = 64). Results: The Tau-A ECLIA was technically robust. Only 1% of the samples was below the detection limit in the ECLIA compared to 10.6% in the ELISA . Tau-A measured in both assays could discriminate between patients with a TBI and non-trauma controls (ELISA: p = 0.0005, ECLIA: p = 0.0002). The increased dynamic range of the Tau-A ECLIA also allowed discrimination between healthy controls from patients with hemorrhagic ( p = 0.0172) and severe ischemic stroke ( p = 0.0118) respectively, as well as patients with mild ischemic stroke from severe ( p = 0.0445). Conclusions: The Tau-A ECLIA was characterized by dynamic range compared to the ELISA, which facilitated a better separation between the patient groups. Tau-A warrants further investigation as a neuronal injury associated marker.